Pengujian Kuat Lentur Balok Beton dengan Tulangan Baja Ringan - Dandi Fahrul Akmal; Eko Walujodjati (Jurnal Konstruksi, 2022)
Reinforced concrete can be prepared in many ways to be lightweight but have high strength. One way to make an alternative to conventional steel reinforcement is to use mild steel. The use of mild steel as an alternative to reinforcement in concrete is still not very popular in the construction sector. Therefore, this research was conducted to determine the flexural strength of reinforced concrete beams with mild steel, as well as the comparison of the flexural strength of reinforced concrete beams with mild steel from the results of research analysis with concrete quality fc' 22 MPa and beam size 20x10 length 90 cm. This study uses an experimental method of testing the flexural strength of concrete with a simple test beam that is loaded with one load, this is intended as a reference and guideline for carrying out flexural strength tests in the laboratory. Starting from material testing to testing compressive strength, split tensile strength and flexural strength. With the results of the average compressive test of concrete with an age of 28 days fc' 12.07 MPa. The value of split tensile strength is usually 8% to 15% of the compressive strength of concrete, while the average value of flexural strength in concrete beams with mild steel reinforcement is 8.78 kN,m and the results of the analysis get 12,302 kN,m. So the results of the test values ​​at the Laboratory are smaller than the results of the analysis.